Detection of human papillomavirus (HPV)-specific T cell response in women with low-grade cervical intraepithelial lesion and HPV vaccinated subjects - Zelini, Paola; Zavaglio, Federica; Dominioni, Mattia; Valsecchi, Marta; Lo Grasso, Lucrezia; d’Angelo, Piera; Giardina, Federica; Romano, Greta; Paolucci, Stefania; Lilleri, Daniele; Cassaniti, Irene; Spinillo, Arsenio; et al. (Frontiers in Immunology, 2026)
BackgroundHuman papillomavirus (HPV) is the most common sexually transmitted infection worldwide and HPV-driven cervical cancers remain a major health concern. This study aimed primarily to develop a test for assessing and characterizing HPV-specific T-cell responses, in HPV-vaccinated women and women with cervical intraepithelial neoplasia (CIN)1.MethodsT-cell responses against HPV-16 and 18 L1, E6, and E7 proteins were evaluated by flow cytometry with a 24h activation-induced marker (AIM) and a 7-day lymphoproliferation (LPR) assays in 18 vaccinated and 60 CIN1 women. HPV genotyping was performed on vaginal swab samples.ResultsLPR assay demonstrated higher sensitivity than AIM. T-cell response was mainly directed against L1 and was higher in CD4+ than CD8+ T cells. All vaccinated women exhibited CD4+ T-cell responses against HPV-16 and to a lesser extent HPV-18 L1. Among CIN1 patients, 46.6% and 33.3% showed HPV-16 and -18 L1-specific CD4+ responses, respectively, even when infected with other HPV strains. Responses were predominantly associated with TH1 and TH17 phenotypes.ConclusionsThe LPR assay is a sensitive tool for detecting HPV-specific T-cell responses. The presence of T-cell responses in CIN1 patients infected with non-16/18 HPVs suggests potential cross-reactivity among HPV genotypes.